2023
DOI: 10.1186/s12931-023-02560-w
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signatures in amniotic fluid at preterm birth and association with bronchopulmonary dysplasia

Birte Staude,
Silvia Gschwendtner,
Tina Frodermann
et al.

Abstract: Background Microbiome dysbiosis can have long-lasting effects on our health and induce the development of various diseases. Bronchopulmonary dysplasia (BPD) is a multifactorial disease with pre- and postnatal origins including intra-amniotic infection as main risk factor. Recently, postnatal pathologic lung microbiota colonization was associated with BPD. The objectives of this prospective observational cohort study were to describe differences in bacterial signatures in the amniotic fluid (AF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Despite a robust rebuttal of these papers, which concluded that the detected microbial DNA was more likely to come from contamination of samples than genuine bacterial colonisation [ 36 ], the possible colonisation of the foetus remains a controversial subject. One recent paper analysing bacterial DNA found in amniotic fluid taken during preterm labour unsurprisingly found a greater bacteria load in these samples compared to amniotic fluid taken from pregnancies with intact membranes when labour was not threatened [ 37 ]. As infection is a risk factor for preterm birth, infants exposed to chorioamnionitis or subject to prelabour rupture of membranes may begin colonisation before birth.…”
Section: Respiratory Microbiota and Cldmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a robust rebuttal of these papers, which concluded that the detected microbial DNA was more likely to come from contamination of samples than genuine bacterial colonisation [ 36 ], the possible colonisation of the foetus remains a controversial subject. One recent paper analysing bacterial DNA found in amniotic fluid taken during preterm labour unsurprisingly found a greater bacteria load in these samples compared to amniotic fluid taken from pregnancies with intact membranes when labour was not threatened [ 37 ]. As infection is a risk factor for preterm birth, infants exposed to chorioamnionitis or subject to prelabour rupture of membranes may begin colonisation before birth.…”
Section: Respiratory Microbiota and Cldmentioning
confidence: 99%
“…A higher rate of the Escherichia / Shigella cluster in infants with moderate/severe CLD was noted, while less severely affected infants had more Ureaplasma spp. and Enterococcus present [ 37 ]. Several studies have demonstrated very low yields of bacterial DNA detection from respiratory samples taken in the first few days of life [ 25 ], indicating that any colonisation of the respiratory tract before birth is likely to be of extremely low biomass and that established and stable communities of organisms are unlikely to present in the airways during foetal life.…”
Section: Respiratory Microbiota and Cldmentioning
confidence: 99%